ISOTHERMS OF PARTICLE ADSORPTION ON MEMBRANES ON ACCOUNT OF ADSORPTION CENTER CHANGES - Arakelyan, V. B.; Aramyan, K. S.; Arustamyan, V. M.; Gevorgyan, H. K.; Karamyan, K. K.; Vardanyan, V. I.; Potikyan, G. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In this work the isotherms of particle adsorption on membranes are evaluated theoretically. The changes of adsorption center structure and the process of particle adsorption are considered in a consistent way. It is shown that the account of potential well deformation at adsorption process may result in qualitatively different regimes of adsorption. Dependence on the parameters of particle interaction with the adsorption center allows to obtain either Longmuir or S-shaped isotherms of adsorption.